A36-dependent actin filament nucleation promotes release of vaccinia virus. - Jacquelyn Horsington; Helena Lynn; Lynne Turnbull; Delfine Cheng; Filip Braet; Russell J Diefenbach; Cynthia B Whitchurch; Guna Karupiah; Timothy P Newsome (PLoS Pathogens, 2013)
Cell-to-cell transmission of vaccinia virus can be mediated by enveloped virions that remain attached to the outer surface of the cell or those released into the medium. During egress, the outer membrane of the double-enveloped virus fuses with the plasma membrane leaving extracellular virus attached to the cell surface via viral envelope proteins. Here we report that F-actin nucleation by the viral protein A36 promotes the disengagement of virus attachment and release of enveloped virus. Cells infected with the A36(YdF) virus, which has mutations at two critical tyrosine residues abrogating localised actin nucleation, displayed a 10-fold reduction in virus release. We examined A36(YdF) infected cells by transmission electron microscopy and observed that during release, virus appeared trapped in small invaginations at the plasma membrane. To further characterise the mechanism by which actin nucleation drives the dissociation of enveloped virus from the cell surface, we examined recombinant viruses by super-resolution microscopy. Fluorescently-tagged A36 was visualised at sub-viral resolution to image cell-virus attachment in mutant and parental backgrounds. We confirmed that A36(YdF) extracellular virus remained closely associated to the plasma membrane in small membrane pits. Virus-induced actin nucleation reduced the extent of association, thereby promoting the untethering of virus from the cell surface. Virus release can be enhanced via a point mutation in the luminal region of B5 (P189S), another virus envelope protein. We found that the B5(P189S) mutation led to reduced contact between extracellular virus and the host membrane during release, even in the absence of virus-induced actin nucleation. Our results posit that during release virus is tightly tethered to the host cell through interactions mediated by viral envelope proteins. Untethering of virus into the surrounding extracellular space requires these interactions be relieved, either through the force of actin nucleation or by mutations in luminal proteins that weaken these interactions.